The effect of the type of sports` mattresses on developing mental skills and tactics for junior fencers - Arnousa, A. (Procedia Engineering, 2012)
The world has witnessed in the recent years a major development in the sector of sports engineering to serve the individual sports, also the importance of mental training has been confirmed by many researcher over the past years. The author recognized that the effect of the nature and components of mattresses on mental training has not yet been studied. So he aimed to identify this effect on the level of mental toughness and tactics for junior fencers.The researcher used the experimental method using pre and post measurements for three variables muscle tension, mental skills and tactical performance. This research was conducted on an intentional sample of junior fencers (n=12) for foil, saber and epee types. After applying the statistical processing on the experiment results, the researcher concluded that using air mattresses during mental training had an impact on the development of mental training skills as well as improving the tactical performance of junior fencers. And using water mattresses during mental training has an impact on improving the tactics for junior fencers. Also using the cotton mattresses had no impact on developing any of the research variables.